Influence of estrogen deficiency on guided bone augmentation: investigation of rat calvarial model and osteoblast‐like MC3T3‐E1 cells. (20th April 2018) - Kubota, Tatsuya; Hasuike, Akira; Tsukune, Naoya; Ozawa, Yasumasa; Yamamoto, Takanobu; Min, Seiko; Naito, Masako; Sato, Shuichi
Abstract : The effect of estrogen deficiency in bone augmentation, and the mechanisms by which estrogen deficiency impedes osteoblast differentiation and collagen matrix production, were examined. Twenty female Jcl:Wistar rats were divided into two groups: ovariectomized rats; and control rats. Guided bone augmentation was performed by positioning plastic caps in the calvarium of all animals at 8 wk after ovariectomy or sham surgery. Micro‐computed tomography and histological sections were used to determine the amount of bone augmentation within the plastic caps. At 8 wk, there was statistically significantly less newly formed bone volume in ovariectomized rats. Immunohistological staining revealed the rare alignment of runt‐related transcription factor 2‐positive osteoblast‐like cells and collagen I‐positive bundle fibers in ovariectomized rats. In cell culture experiments, pre‐osteoblast‐like cells, MC3T3‐E1, were treated with the estrogen receptor antagonist, fulvestrant. In treated cells, alkaline phosphatase activity remained high, whereas Alizarin Red staining was completely inhibited. Extracellular staining intensity of collagen I was decreased after fulvestrant treatment. Consistent with these observations, gene‐expression analysis confirmed that fulvestrant treatment led to weaker expression of mRNA for osteogenic transcription factors and bone matrix protein‐related genes. The results demonstrate that estrogen deficiency suppresses osteoblast differentiation and collagen matrix production in bone augmentation.